Epigastric pain: incarceration or rotation? - Carvalho, Ana Raquel Franky Gomes (2015)
Introduction: Acute intrathoracic gastric volvulus occurs when the stomach has a twist mesenteroaxial/organoaxial or chest cavity resulting in a dilatation or rupture of the diaphragmatic hiatus or diaphragmatic hernia. The purpose of this work is to show a interesting case of gastric volvulus in a patient with several comorbidities. Case Report: A 77-year-old female with past history of hiatal hernia and mental disease associated with diabetes and atrial fibrillation. Patient went to the emergency department due to vomiting associated with blood. Analytical parameters (WBC, HGB, PCR, metabolic panel and liver function), showed no significant alterations. Thoracic X-ray revealed an enlarged mediastinum due to herniation of the stomach. A computed tomography (CT) scan confirmed intrathoracic localization of the gastric antrum with twist. Patient’s symptoms were relieved by nasogastric intubation and analgesia. After six months, the patient is still asymptomatic. Conclusion: In general, the treatment of an acute gastric volvulus requires an emergent surgical repair. In patients who are not surgical candidates (with comorbidities or an inability to tolerate anesthesia), endoscopic reduction should be attempted. Chronic gastric volvulus may be treated non-emergently, and surgical treatment is increasingly being performed using a laparoscopic approach. In this case, it is a chronic form that was solved with the placement of the nasogastric tube. A nasogastric decompression is an option in the chronic form of hiatal hernia associated to gastric volvulus in patients with serious comorbidities.